The impact of COVID-19 on the provision of respectful maternity care: Findings from a global survey of health workers. Issue 4 (July 2022) - Asefa, Anteneh; Semaan, Aline; Delvaux, Therese; Huysmans, Elise; Galle, Anna; Sacks, Emma; Bohren, Meghan A.; Morgan, Alison; Sadler, Michelle; Vedam, Saraswathi; Benova, Lenka
Abstract: Background: Significant adjustments to maternity care in response to the COVID-19 pandemic and the direct impacts of COVID-19 can compromise the quality of maternal and newborn care. Aim: To explore how the COVID-19 pandemic negatively affected frontline health workers' ability to provide respectful maternity care globally. Methods: We conducted a global online survey of health workers to assess the provision of maternal and newborn healthcare during the COVID-19 pandemic. We collected qualitative data between July and December 2020 among a subset of respondents and conducted a qualitative content analysis to explore open-ended responses. Findings: Health workers (n = 1127) from 71 countries participated; and 120 participants from 33 countries provided qualitative data. The COVID-19 pandemic negatively affected the provision of respectful maternity care in multiple ways. Six central themes were identified: less family involvement, reduced emotional and physical support for women, compromised standards of care, increased exposure to medically unjustified caesarean section, and staff overwhelmed by rapidly changing guidelines and enhanced infection prevention measures. Further, respectful care provided to women and newborns with suspected or confirmed COVID-19 infection was severely affected due to health workers' fear of getting infected and measures taken to minimise COVID-19 transmission. Discussion: Multidimensional and contextually-adapted actions are urgently needed to mitigate the impacts of the COVID-19 pandemic on the provision and continued promotion of respectful maternity care globally in the long-term. Conclusions: The measures taken during the COVID-19 pandemic had the capacity to disrupt the provision of respectful maternity care and therefore the quality of maternity care.